Tari Serampang Dua Belas: Analisis Pertunjukan dan Pemaknaan Tari di Kota Medan - Nasution, Abdul Gani Jamora; Syahfitri, Andini; Mustika, Nikmah; Lubis, Pinta Rojulani; Ritonga, Wilda Rahmayani (At-Tadris: Journal of Islamic Education, 2023)
The Serampang Dua Twelve Dance, which is a Malay dance originating from North Sumatra, in the Malay Deli Land, is very different from other Malay dances of the same family. It was first shown in 1952 in Medan City. In subsequent performances, this Serampang Twelve Dance can enter the international world. So that at that time President Soeharto was interested and decided that the Deli Malay dance would become a national dance. Guru Suati as the famous pioneer of the Serampang Twelve dances. Incorporating various cultures from various cultures in the city of Medan at that time. The attitude of maintaining and strengthening Malay culture is highly demonstrated in the tarain which currently stands out as a complement to the meaning in the dance. In this study, the authors used a descriptive qualitative method, taking into account secondary and primary interests. From this research method, it is hoped that it can solve problems related to this research, so that the objectives of this research are achieved. The purpose of this study is to find out more about the various dance movements that support the performance and convey meaning in the Serampang Dua dance, from the perspective of the dancers' perfection in the city of Medan.